Comparison of platelet function and platelet parameters of apheresis platelet using platelet additive solution and without platelet additive solution - Adzahar, Sumaiyah (2021)
Introduction: Platelet additive solution (PAS) is a crystalloid nutrient media practically used to replace and reduce approximately two-thirds of plasma in platelet product. It is an alternative medium intended to maintain good quality of platelets with longer shelf life. Objective: The aim of this study is to compare the platelet function and platelet parameters of apheresis platelets store in PAS as the treated group and without PAS (plasma) which is the standard practice as a control group. Study design and methods: An interventional study was conducted involving apheresis blood donors in Unit Perubatan Transfusi, Hospital USM from February 2019 until June 2019, and a total of 20 apheresis blood donors that fulfilled the inclusion and exclusion criteria were selected. Apheresis platelets were collected using Amicus cell separator and were stored in PAS and without PAS for seven days. Platelet parameters including platelet count, mean platelet volume (MPV), platelet distribution width (PDW), platelet morphological assessment using light microscopy, platelet aggregation test and pH were measured on day one and day seven of storage in PAS and without PAS. The statistical analysis used for these parameters was repeated measures ANOVA. Other parameters such as ABO antibody titer was measured only on day one of storage and was analyzed using Wilcoxon Signed Ranks test. The bacterial cultures were carried out on day seven of storage and analyzed using Chi-square test. A p value of <0.05 which was considered statistically significant. Results: Majority of the apheresis donor was Malay male. The average platelet count of apheresis platelets was between 3.0 – 4.0 x1011/unit. There were significant differences in the MPV (day 7, p=0.004), platelet aggregation test with arachidonic acid (day 7, p=0.001), collagen (day 1, p=0.011) and epinephrine (day 1, p=0.005; day 7, p=0.041), platelet morphology (day 1 and day 7, p=0.041), pH (day 1, p=0.014; day 7, p=0.002) and ABO antibody titers (anti-A, p=0.002; anti-B p=0.004) between apheresis platelet in PAS and without PAS. Other platelet parameters were statistically not significant. Conclusion: The apheresis platelets stored in PAS demonstrated inferior findings in most study parameters compared to without PAS, while the study of antibody titer in PAS showed superior results compared to without PAS. The platelet morphology and function were better maintained in plasma (without PAS) compared to in PAS. However, this study needs to be confirmed with more samples and include in-vivo study in the future.